Climate trauma : foreseeing the future in dystopian film and fiction - Kaplan, E. Ann (New Brunswick, New Jersey : Rutgers University Press, 2016)
Examining a variety of films that imagine a catastrophic future, from Children of Men to The Book of Eli, E. Ann Kaplan considers how they have exacerbated our sense of impending dread, triggering what she terms "Pretraumatic Stress Disorder." But Climate Trauma also explores ways these films might help us productively engage with our anxieties about climate change, giving us a prophetic glimpse of the terrifying future selves we might still work to avoid becoming.
Prologue: Climate trauma and Hurricane Sandy -- Introduction: Pretrauma imaginaries: theoretical frames -- Trauma studies moving forward: genre and pretrauma cinema -- Pretrauma climate scenarios: Take shelter, The happening, and The road -- Pretrauma political thrillers: Children of men-with reference to Soylent green and The handmaid's tale -- Memory and future selves in pretrauma fantasies: The road and The Book of Eli -- Microcosm: politics and the body in distress in blindness and The Book of Eli -- Getting real: traumatic climate documentaries: into eternity and manufactured landscapes -- Afterword: humans and eco- (or is it sui-?) cide -- Filmography.
Includes bibliographical references (pages 173-185), filmography (pages 187-189) and index.
Print version record.
JSTOR
Keywords: Dystopian films -- History and criticism; Climatic changes in motion pictures; Psychic trauma in motion pictures; Future, The, in motion pictures; Films dystopiques -- Histoire et critique; Climat -- Changements, au cinéma.; Traumatisme psychique au cinéma.; Futur au cinéma.; PERFORMING ARTS -- Reference; PHILOSOPHY -- Movements -- Critical Theory; Climatic changes in motion pictures; Dystopian films; Future, The, in motion pictures; Psychic trauma in motion pictures; Criticism, interpretation, etc